2021
DOI: 10.14309/ajg.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Are All Endoscopy-Related Musculoskeletal Injuries Created Equal? Results of a National Gender-Based Survey

Abstract: INTRODUCTION: Endoscopy-related injury (ERI) is common in gastroenterologists (GI). The study aim was to assess the prevalence of self-reported ERI, patterns of injury, and endoscopist knowledge of preventative strategies in a nationally representative sample. METHODS: A 38-item electronic survey was sent to 15,868 American College of Gastroenterology physician members. The survey was completed by 1,698 members and was included in analyses. Descriptive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
85
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 28 publications
5
85
0
5
Order By: Relevance
“…In this issue of Clinical Endoscopy, Kamani et al [ 3 ] presented a study on the prevalence of endoscopy-related musculoskeletal pain (ERMP) in endoscopists, comparison of ERMP between endoscopists and non-endoscopists, and the risk factors associated with the pain in endoscopists. They reported that the prevalence of ERMP in endoscopists was higher than that in non-endoscopists (95.08% vs. 54.83%), which was higher than that reported in other studies [ 2 ]. This discrepancy might be due to the different study designs or different questionnaires used.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…In this issue of Clinical Endoscopy, Kamani et al [ 3 ] presented a study on the prevalence of endoscopy-related musculoskeletal pain (ERMP) in endoscopists, comparison of ERMP between endoscopists and non-endoscopists, and the risk factors associated with the pain in endoscopists. They reported that the prevalence of ERMP in endoscopists was higher than that in non-endoscopists (95.08% vs. 54.83%), which was higher than that reported in other studies [ 2 ]. This discrepancy might be due to the different study designs or different questionnaires used.…”
mentioning
confidence: 62%
“…In particular, procedural physicians and surgeons are at a high risk of WRMDs that may be harmful to their lives and influence the quality and quantity of patient care [ 1 ]. Gastroenterologists performing endoscopy are also at a high risk of WRMDs, and the prevalence of endoscopy-related injuries has been reported as 75% in a previous study [ 2 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations